The Effect Of Intrinsic Motivation And Work Stress On Performance Of Employee Pizza Hut Merr Surabaya - Mochammad Fajar (NAROTAMA UNIVERSITY, Indonesia, 2019)
The purpose of this study is 1. To analyze work motivation on employee performance 2. To analyze work performance with employees 3. To analyze employee performance at Pizza Hut Merr Surabaya. This research is quantitative research. The population and samples were distributed by 47 respondents. Data collection techniques using a questionnaire. The data analysis used is the Statistical Package for Social Sciences (SPSS). The results of the study showed the effect of the Intrinsic Motivation Variable (X1) on employee performance (Y) showed a significant amount of 0,000. And Job stress variable (X2) on Employee Performance (Y) shows no significant value of 0.083.The results of this study indicate that compared to work stress, intrinsic motivation has a stronger dancer on employee performance at Pizza Hut Merr Surabaya.